Antimicrobial resistance of Streptococcus spp. in different hospital units - Kaytukov A.O.; Glushkova E.V.; Briko N.I.; Kryzhanovskiy V.G.; Salmina T.A.; Orlova O.E.; Kashirina A.Yu. (Клиническая микробиология и антимикробная химиотерапия)
Objective.